The Empowering Human Resources Academically Based On Bilingual Environment At Pesantren Al Multazam and Darut Taqwa Mojokerto by Using Asset-Based Community Development (ABCD) Approach - Prastyo, Hari; Rinda, Rinda; Wahyudi, Imam (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2024)
This article describes a community outreach program that aims to teach human rights in an impartial manner inside a multilingual environment at Mojokerto, that are Pesantren Al Mulatzam and Darut Taqwa. This project used conceptualisation of Aset-Based Community Development (ABCD) to develop aset as language tutors, bilingual communities, and Pesantren environs. The main cognitive content is to improve the curriculum and bilingual text books while analyzing the goals, restraint, and project strategy. This article also summarizes previous research on the project of fundamental quantity national participation. The topics included the role of human resources management, the theatrical role of heutagogy in primary education, bilingual education, and speech communication in primary schools. Moreover, the project has been presented at Pesantren Al Mulatzam and Darut Taqwa of Mojokerto for research on Human Education with a Multilingual Environment.